High thermoelectric properties achieved in environmentally friendly sulfide compound Bi2SeS2 by nanoenginnering. (October 2021) - Li, Fu; Ruan, Min; Jabar, Bushra; Liang, Chongbin; Chen, Yuexing; Ao, Dongwei; Zheng, Zhuanghao; Fan, Ping; Liu, Weishu
Abstract: The sulfide compound Bi2 SeS2 is an environmentally friendly thermoelectric material, which is as an analogy of the traditional compound Bi2 S3 . Here, a high ZT value of 1.04 at 773 K is obtained through synergistically tuning the electrical transport properties by using Cu and I as the dual carrier providers and suppressing the lattice thermal conductivity by forming the Cu-rich nano-precipitates. The dual carrier providers lead to exclusively high electrical conductivity and hence a large power factor over 650 μWm −1 K −2 at 773 K. The atomic resolved annular dark field STEM reveals the interstitial Cu and S deficiency would result into the formation of BiCuS2 or Cu2 S nano-precipitates and embed in the lattice of Bi2 SeS2, serving as strong phonon scattering. This work suggested that nanostructured Bi2 SeS2 is very promising for waste heat energy harvesting in the future. Graphical Abstract: A high ZT of 1.04 at 773 K is achieved in the sulfide compound of Bi2 SeS2 by synergistically tuning electrical transport properties by using Cu and I as the dual carrier providers and suppressing the lattice thermal conductivity by forming the Cu-rich nano-precipitates and defects. ga1 Highlights: A high ZT of 1.04 at 773 K is achieved in the sulfide compound of Bi2 SeS2 with environmentally friendly composition. The dual carrier providers of Cu and I lead to exclusively high electrical conductivity and hence a large power factor. Cu-rich nano-precipitates serve as strong phonon scattering, causing a low lattice thermal conductivity.